Competency, Entrepreneurial Leadership, Commitment and Their Impact on Performance through Village Governance - Haris Fauzi; Atty Tri Juniarti; Iman Sudirman (Jurnal Manajemen Bisnis, 2023)
This research utilizes descriptive analysis and confirmation methods. The data collection technique used is by distributing questionnaires. The population in this study were village chiefs in the CIAYUMAJAKUNING (Cirebon, Indramayu, Majalengka, and Kuningan) area, with a representative of 312 respondents. The sampling technique used is Cluster Proportionate Stratified Random Sampling. The scale of proportions in this study uses a Likert scale. Testing of data instruments is carried out by testing the validity and reliability tests, while the data analysis is done by using the SEM analysis tool. The results of the research that has been done show competence, entrepreneurial-minded leadership, commitment in good criteria, and village governance and village head performance in good criteria. The study results partially show that competency, entrepreneurial leadership, and commitment have a significant effect on village governance, then village governance has a significant effect on village head performance. The results of the study simultaneously state that competency, entrepreneurial leadership, and commitment together have a significant effect on village governance.